1974
DOI: 10.1128/aem.27.1.192-196.1974
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Neisseria gonorrhoeae by a Factor Produced by Candida albicans

Abstract: When Candida albicans is present on Transgrow specimens, Neisseria gonorrhoeae is detected less frequently or else can be seen in Gram stains but cannot be readily cultured. When C. albicans and N. gonorrhoeae are grown together on Transgrow, the gonococcal cells die off much more readily than N. gonorrhoeae grown on Transgrow alone. By use of a cross-streaking technique on agar plates, it has been demonstrated that C. albicans produces a soluble substance inhibitory to N. gonorrhoeae, although not to other mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…The largest percentage of strains of streptococci were inhibitory, fol- (21) Infected lowed by staphylococci and lactobacilli. Other studies using a variety of techniques have demonstrated the in vitro antagonism of N. gonorrhoeae by Candida albicans, staphylococci, Corynebacteria, streptococci, other species of Neisseria, Enterobacteriaceae, and Pseudomonas aeruginosa (10,17,20,24,25,27,30,34). However, very few of these studies provided direct evidence for a protective effect in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…The largest percentage of strains of streptococci were inhibitory, fol- (21) Infected lowed by staphylococci and lactobacilli. Other studies using a variety of techniques have demonstrated the in vitro antagonism of N. gonorrhoeae by Candida albicans, staphylococci, Corynebacteria, streptococci, other species of Neisseria, Enterobacteriaceae, and Pseudomonas aeruginosa (10,17,20,24,25,27,30,34). However, very few of these studies provided direct evidence for a protective effect in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…gonorrhoeae. Similar inhibition was caused by C. albicans [4] and a number of anaerobes commonly found in the urogenital flora [5]. The nature of these inhibitors of N. gonorrhoeae is less clear but both susceptibility to bacteriocins [6] and shortchain fatty acids [7] have been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…In about 30% of the total isolations, C. albicans was recovered, together with bacteria like enterobacteriaceae, enterococci, staphylococci and 6-haemolytic streptococci. In 8 cases, Neisseria gonorrhoeae was also grown although concomitant isolation of C. albicans and gonococci are reported to be rare owing to an inhibitory factor produced by C. albicans (7). Trichomonas vaginalis was detected in only 5 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Morever, it is often difficult to assess the significance of these isolations, particularly in the asymptomatic patient. In the past, high frequencies of isolation from hospital patients have led many authors to regard vaginal yeasts as harmless commensals (4, 5,7). Some prospective studies (1,8), however, have shown that yeasts were not recovered from the normal population as frequently as was generally believed, and their presence, particularly in pregnant women, requires careful consideration for therapy.…”
Section: Introductionmentioning
confidence: 99%